Study of Mineral Content in Pond Water for Traditional Farming of Black Tiger Shrimp (Penaeus monodon) in Tarakan City - Simon, Serianto; Maulianawati, Diana (Aquatic Life Sciences, 2025)
Although required only in trace amounts, minerals are vital for the cultivation of black tiger shrimp (Penaeus monodon). However, limited studies have explored the link between mineral availability and shrimp farming performance. This study aimed to identify the types and concentrations of minerals present in shrimp ponds located in two different areas of Tarakan City, North Kalimantan, namely West Tarakan and East Tarakan districts. An exploratory approach was employed, and samples were collected using purposive sampling techniques. The analysis revealed that concentrations of Magnesium (Mg), Calcium (Ca), and Iron (Fe) in both ponds met the quality standards suitable for shrimp farming. In Pond 1, Mg levels ranged from 1200 to 1245 mg/L, Ca from 438 to 480 mg/L, and Fe was below 0.02 mg/L. Similarly, in Pond 2, Mg levels ranged from 1200 to 1290 mg/L, Ca from 432 to 480 mg/L, and Fe remained below 0.02 mg/L. These values indicate that the presence of these minerals poses no toxicity risk to shrimp culture environments. Furthermore, water quality parameters such as temperature, salinity, pH, and dissolved oxygen were within the acceptable range for P. monodon cultivation. No significant correlation was found between water quality and mineral concentrations. Harvest results showed a yield of 90 kg (average size 35) with a 90% survival rate in Pond 1, from an initial stocking of 3,000 post-larvae. In contrast, no shrimp were harvested from Pond 2, and the absence of yield was attributed to suspected predation, as no disease outbreak or mass mortality was observed. These findings highlight the importance of stable mineral conditions in supporting successful shrimp farming, and suggest further investigation into non-water quality factors such as predation.